H2S-Induced Sulfhydration: Biological Function and Detection Methodology - Zhang, Da; Du, Junbao; Tang, Chaoshu; Huang, Yaqian; Jin, Hongfang (Frontiers in Pharmacology, 2017)
At appropriate concentrations, hydrogen sulfide, a well-known gasotransmitter, plays important roles in both physiology and pathophysiology. Increasing evidence suggests that modifying thiol groups of specific cysteines in target proteins via sulfhydration or persulfidation is one of the important mechanisms responsible for the biological functions of hydrogen sulfide. A variety of key proteins of different cellular pathways in mammals have been reported to be sulfhydrated by hydrogen sulfide to participate and regulate the processes of cell survival/death, cell differentiation, cell proliferation/hypertrophy, cellular metabolism, mitochondrial bioenergetics/biogenesis, endoplasmic reticulum stress, vasorelaxtion, inflammation, oxidative stress, etc. Moreover, S-sulfhydration also exerts many biological functions through the cross-talk with other post-translational modifications including phosphorylation, S-nitrosylation and tyrosine nitration. This review summarizes recent studies of hydrogen sulfide-induced sulfhydration as a posttranslational modification, an important biological function of hydrogen sulfide, and sulfhydrated proteins are introduced. Additionally, we discuss the main methods of detecting sulfhydration of proteins.